Situational Analysis : Improving Economic Outcomes by Expanding Nutrition Programming in the Kyrgyz Republic - World Bank; UNICEF (World Bank, Washington, DC, 2017)
The World Bank and The United Nations Children's Fund (UNICEF) jointly developed this report to calculate the potential human and economic benefits to be gained from increasing nutrition investments in the Kyrgyz Republic. This report provides compelling evidence of the potential to improve health and economic outcomes through scaling up effective nutrition interventions and introducing new proven interventions to reduce the direct causes of under nutrition in order to support the Kyrgyz government's commitment to the well-being and prosperous future of the Kyrgyz people. This situational analysis examines and quantifies the scope of under nutrition in the Kyrgyz Republic by presenting: (1) the epidemiology of under nutrition; (2) an estimate of the health consequences of under nutrition in terms of mortality and disability adjusted life years (DALYs), and the economic losses due to lost workforce and productivity; (3) the health, social protection, and agriculture and food intervention systems relevant to delivering interventions for improving nutrition; (4) the current coverage of nutrition interventions; and (5) the potential economic gains achievable by scaling up effective nutrition interventions. The current context is very favorable for scaling up nutrition interventions in the Kyrgyz Republic. Investing in nutrition has increasingly proven to have excellent development and health returns. The international development community has recognized (1) the need to scale up nutrition interventions; (2) the potential for public-private partnerships; and, (3) a growing consensus around a common framework for action. Reducing under nutrition worldwide is a priority for the World Bank and UNICEF, and also critical to achieving the Millennium Development Goals (MDGs).